Categories in context: gender and work in France and Germany, 1900-present - Bender, Anne-Françoise; Berrebi-Hoffmann, Isabelle; Berrebi-Hoffmann, Isabelle; Bussmann, Maike; Giraud, Olivier; Giraud, Olivier; Höroldt, Carolin; Lallement, Michel; Lechevalier, Arnaud; Müller, Katja Karolin; Reigné, Philippe; Renard, Léa; et al. (International studies in social history, 2019)
Despite the wealth of empirical research currently available on the interrelationships of gender and labor, we still know comparatively little about the forms of classification and categorization that have helped shape these social phenomena over time. Categories in Context seeks to enrich our understanding of how cognitive categories such as status, law, and rights have been produced, comprehended, appropriated, and eventually transformed by relevant actors. By focusing on specific developments in France and Germany through a transnational lens, this volume produces insights that can be applied to a wide variety of political, social, and historical contexts